Case Study: Science and Innovation Diplomacy Agencies at the nexus of research, economics, and politics - Nicolas Rüffin (Institute for European Studies, 2018)
The last decade has seen the emergence of several organisations dedicated to pursue national science diplomacy agendas. Among others, countries like the UK, Switzerland, Germany, the Netherlands, and Denmark established science and innovation diplomacy agencies. We comparatively examine three cases: The UK's Science and Innovation Network, the Swiss SWISSNEX, and the Danish Innovation Centre Denmark. We look for similarities and dissimilarities in terms of organisational setup, locations, governance and funding, topics and objectives, and tasks. We put forward three analytical dimensions that shape the organisations' activities. Tensions between headquarters and periphery determine the range of possible activities on the ground. Agencies have to deal with challenges arising from the different mind-sets of diplomats and scientists. Last, but not least, the organisations have to decide whether to primarily engage either in the promotion of (basic) science or in the commercial application of research. The three cases each feature distinct characteristics. While SWISSNEX and Innovation Centre Denmark have a strong take on the promotion of domestic research, innovation, and products, UK's network engages in a broader spectrum of activities and topics at the nexus of science, economics, and foreign policy objectives. Despite differences in their objectives and organisational setup, all agencies have established offices at hotbeds of science and innovation—particularly in the BRICS—, carry out similar tasks on the ground, and focus on comparable topics. A lack of reliable performance indicators hampers the assessment of individual agencies and outposts, thus making it difficult to judge the success of the respective agencies. While the agencies have developed an integrative narrative of innovation as encompassing all activities from basic research to commercial application, officers on the ground predominantly pursue their goals against the backdrop of a linear model of innovation, focusing either on fundamental research or on applying scientific insights into business opportunities. It is unlikely that many new offices will be established in the near future. Most likely, additional growth will be triggered when emerging economies like Brazil, India, or China start to establish their own science diplomacy agencies.
Keywords: 330; science diplomacy; innovation; agencies; Europe; SWISSNEX; UK's Science and Innovation Network; Innovation Centre Denmark; BRICS